THREAT ASSESSMENT AND MANAGEMENT: PROTOCOL AND BUDGETARY NEEDS FOR TOOLS AND MEMBER TRAINING IN HIGHER EDUCATION - Barfield, Patricia L (East Carolina University, 2021)
The primary goal of threat assessment is to prevent individuals who are on a pathway to violence. Threat assessment entails a three-step process beginning with identifying a concern, assessing the risk and managing the posed threat (Vossekuil, United States. Department of Education, & United States. Secret Service, 2002). A southeastern public university has a threat assessment policy that needs revision and full implementation to improve processes and budgetary needs for threat assessment tools and member training. The purpose of this mixed methods study was to collect and analyze information that was to be used to create a revised and fully implemented threat assessment policy at a southeastern university system and a baseline TAM team protocol for other institutions to consider adapting to fit their campus needs.This study surveyed threat assessment and management team members at the study institution and conducted remote semi-structured interviews by phone with threat assessment chairs from three additional public southeastern universities to collect data on the threat assessment policy, processes, and budgetary needs for training and tools at the study university. Qualitative data was collected from both the semi-structured interviews and the open-ended questions in the survey. Quantitative data was collected in order to determine the ideal amount of new member training, on-going training and best-practice threat assessment tools.The results from the mixed methods study indicated that universities within a southeastern public system varied with policy, funding, threat assessment tools, and specialized member training. It is recommended that the southeastern university public system implement a baseline for institutions to consider mirroring based on best practices regarding funding, new member and consistent specialized member training and threat assessment tools to appropriately assess and mitigate campus threats.
Keywords: Threat Assessment and Management; Universities and colleges--Security measures; School violence--Prevention